Pro HTML5 accessibility - O Connor, Joshue. (Apress, 2012)
Pro HTML5 Accessibility helps designers come to grips with building exciting, accessible and usable web sites and applications with HTML5. The book covers how to use HTML5 in order to serve the needs of people with disabilities and older persons using assistive technology (AT). It aims to be a useful ‘go-to’ guide, providing practical advice. It takes several approaches, including a look at the new semantics of HTML5 and how to combine its use with authoring practices you know from using earlier versions of HTML. It also demonstrates how HTML5 content is currently supported (or not) by assistive technologies such as screen readers, and what this means practically for accessibility in your web projects. The HTML5 specification is huge, with new APIs and patterns that can be difficult to understand. Accessibility can also seem complex and nuanced if you have no experience interacting with people with disabilities. This book walks you though the process of designing exciting user interfaces that can potentially be used by everyone, regardless of ability. Accessibility is really a quality design issue, and getting it right is often more a matter of approach than having sophisticated, cutting-edge tools at your disposal. This book will be your companion in your journey to understand both HTML5 and accessibility, as the author has many years of experience as a designer and web developer working directly with people with all types of disabilities. He has been involved with the development of HTML5 from an accessibility perspective for many years, as a member of the W3C WAI Protocols and Formats working group (which is responsible for ensuring W3C specifications are serving the needs of people with disabilities) as well as the HTML5 Working Group itself. Introduces the new HTML5 specification from an accessibility perspective Shows how incorporating accessibility into your interfaces using HTML5 can have benefits for all users Explains how HTML5 is currentlyed by assistive technologies like screen readers, and how to work around these limitations when developing.